Pengembangan dan Intervensi Melalui Buku Saku Digital Gema Bahasa dalam Peningkatan Literasi Bahasa pada Mahasiswa - Virgin, Jesica Maranatha; Putra, Dimas Setyadi (Fisip UIN Sunan Gunung Djati Bandung, 2025)
The Programme for International Student Assessment (PISA) report shows a very low literacy level in Indonesian people, ranking 72 out of 77, indicating a critical need for language improvement. Language and communication are integral to students' daily activities, yet many struggle with both verbal and non-verbal aspects of written language. A pre-survey conducted on 149 students in East Java revealed that 88.6% frequently encountered language errors. To address this issue, researchers launched the Gerakan Mahasiswa Berbahasa (Gema Bahasa), an initiative promoting language literacy through socialization and the development of a language pocketbook for university student organizations. This program, conducted from March to April 2024, involved 20 students. Results showed a significant increase in literacy knowledge, with pretest scores averaging 24.5 and post-test scores rising to 94 after intervention. All participants (100%) expressed the need for electronic books for easier access and distribution. This feedback was accommodated through a QR code linked to the digital version. However, further refinement of the Gema Bahasa Pocket Book is necessary, requiring collaboration with linguists and policymakers to enhance its content and effectiveness for broader implementation.